A multiply substituted G–H loop from foot-and-mouth disease virus in complex with a neutralizing antibody: a role for water molecules - Ochoa, Wendy F.; Kalko, Susana G.; Mateu, Mauricio G.; Gomes, Paula; Andreu, David; Domingo, Esteban; Fita, Ignasi; Verdaguer, Nuria (Journal of General Virology, 2000)
The crystal structure of a 15 amino acid synthetic peptide, corresponding to the sequence of the major antigenic site A (G–H loop of VP1) from a multiple variant of foot-and-mouth disease virus (FMDV), has been determined at 2·3 Å resolution. The variant peptide includes four amino acid substitutions in the loop relative to the previously studied peptide representing FMDV C-S8c1 and corresponds to the loop of a natural FMDV isolate of subtype C1. The peptide was complexed with the Fab fragment of the neutralizing monoclonal antibody 4C4. The peptide adopts a compact fold with a nearly cyclic conformation and a disposition of the receptor-recognition motif Arg–Gly–Asp that is closely related to the previously determined structure for the viral loop, as part of the virion, and for unsubstituted synthetic peptide antigen bound to neutralizing antibodies. New structural findings include the observation that well-defined solvent molecules appear to play a major role in stabilizing the conformation of the peptide and its interactions with the antibody. Structural results are supported by molecular-dynamic simulations. The multiply substituted peptide developed compensatory mechanisms to bind the antibody with a conformation very similar to that of its unsubstituted counterpart. One water molecule, which for steric reasons could not occupy the same position in the unsubstituted antigen, establishes hydrogen bonds with three peptide amino acids. The constancy of the structure of an antigenic domain despite multiple amino acid substitutions has implications for vaccine design.